Orthogonal experiments and bonding analysis of ultrasonic welded multi-layer battery foils and tabs - Lun Zhao; Jianxiong Su; Jiguang Li; Zeshan Abbas; Haiping Dai; Long Ma (Engineering Science and Technology, an International Journal, 2024)
The motivation for this research stems from the growing demand for solid-phase welding technology to join multilayers metals, particularly in green electric vehicles. Welding of foils and tabs inside battery is a challenging task due to poor joint formation at the interface and low strength. Ultrasonic welding is an efficient, reliable and environmentally friendly bonding method to firmly connect multi-layer copper foils and tabs. Therefore, this is used to achieve electrical bonding within the lithium-ion batteries. This is widely used in production of new energy vehicle batteries. In this work, 40 layers of copper foil were bonded to 0.3 mm nickel-plated copper tabs using ultrasonic metal welding technology. The effect of ultrasonic welding parameters on T-peel strength of joints was systematically investigated by orthogonal experimental design. The maximum T-peel strength of 359.17 N was obtained under optimal parameters (e.g., welding energy 600 J, pressure 0.3 MPa and amplitude 55 %). The variation of welding temperature and amplitude under different welding parameters was measured using infrared thermometer and laser vibrometer. Moreover, the surface, cross-sectional and failure fracture analysis and characterization of specimens with different weld qualities were performed using optical microscopy and scanning electron microscopy (SEM). In addition, the state of Ni layer in cross-section was analyzed using the energy dispersive spectroscopy (EDS) technique after ultrasonic welding. This approach can be straightforward and more appropriate to the development of solid-phase welding method for automotive industry.